2020
DOI: 10.1177/1759091420962695
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Abnormalities Provide New Insight on the Neural Mechanisms Underlying the Sleep-Arousal Phase Dysfunctions in Sudden Infant Death Syndrome

Abstract: The purpose of this study was to research possible developmental alterations of the substantia nigra (SN) in sudden infant death syndrome (SIDS), a syndrome frequently attributed to arousal failure from sleep. Brain stems of 46 victims of sudden infant death, aged from 1 to about 7 months (4 to 30 postnatal weeks), were investigated. Twenty-six of these cases were diagnosed as SIDS, due to the lack of any pathological finding, while the remaining 20 cases in which the cause of death was determined at autopsy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…The hazardous effects of exposure to tobacco smoking, whether active or passive, during pregnancy include placenta previa (Shobeiri and Jenabi, 2017), placental abruption (Ananth et al, 2016), ectopic pregnancy, early membrane rupture, low birth weight (Bar-Zeev and Solt, 2018), premature birth, sudden perinatal deaths, and stillbirths (Lavezzi et al, 2017;Anderson et al, 2019). We have highlighted these aspects in previous studies as well (Lavezzi et al, 2010(Lavezzi et al, , 2011(Lavezzi et al, , 2020Mehboob, 2017;Mehboob et al, 2017;Muhammad et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…The hazardous effects of exposure to tobacco smoking, whether active or passive, during pregnancy include placenta previa (Shobeiri and Jenabi, 2017), placental abruption (Ananth et al, 2016), ectopic pregnancy, early membrane rupture, low birth weight (Bar-Zeev and Solt, 2018), premature birth, sudden perinatal deaths, and stillbirths (Lavezzi et al, 2017;Anderson et al, 2019). We have highlighted these aspects in previous studies as well (Lavezzi et al, 2010(Lavezzi et al, , 2011(Lavezzi et al, , 2020Mehboob, 2017;Mehboob et al, 2017;Muhammad et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…A study by Lavezzi et al recently described low tyrosine hydroxylase expression in SIDS cases associated with a delayed development of Substantia Nigra pars compacta (SNpc). Moreover, nicotine absorption in the uterus was related to decreased neuron density in SN [83]. SNpc represents the major dopamine brain center with an important role in regulation of the sleep-arousal cycle [84].…”
Section: The Brainstem Hypothesis In Sidsmentioning
confidence: 99%
“…SNpc represents the major dopamine brain center with an important role in regulation of the sleep-arousal cycle [84]. Therefore, the deficit of dopaminergic neurons, alongside with smoking exposure, may explain SIDS occurrence in the awakening phase in a significant number of cases [83].…”
Section: The Brainstem Hypothesis In Sidsmentioning
confidence: 99%
“…It has been demonstrated that alveolar bleeding does not correlate with hemorrhage of the nose/mouth or with intrathoracic hemorrhagic petechiae in cases of sudden infant death with adequate sleeping conditions (Krous et al, 2007;Lavezzi et al, 2020;Osawa et al, 2020). Heart tissue samples obtained from the left ventricle show T cell infiltrates that require further immunochemistry and/or biomolecular testing to diagnose acute fatal myocarditis (Bajanowski et al, 2007).…”
mentioning
confidence: 99%